Hidden in Plain Sight: Saroy of TT 233 in the Tomb of Samut-Kyky (TT 409) - Chapman, David W. (Zeitschrift für ägyptische Sprache und Altertumskunde, 2022)
Attention is drawn to the official named Saroy with the title Overseer of the Hunters of Amun in the context of the banquet scene in the Ramesside tomb of Samut-Kyky (TT 409). This leads to a critical assessment of all the evidence to see whether it is plausible that the Saroy in TT 409 is the official known as the owner of TT 233 and the statues CG 42167 and 42168 in the Cairo Museum.